A cross-cultural study of the effect of parental bonding on the perception and response to criticism in Singapore, Italy and USA - Neoh, Michelle Jin-Yee (2022)
Parents play a primary and crucial role in emotional socialisation processes in children where individuals learn the expression, understanding and regulation of emotions. Parenting practices and dimensions of the parent-child relationship have been associated with social and emotional processes in children. As criticism involves negative emotional reactions and emotion regulation, the parent-child relationship is likely to influence an individual's perception and response to criticism. Hence, the present study investigated the relationship of parental bonding and the perception and response to criticism in three different countries-Singapore, Italy and USA. Adult participants (n = 444) completed the Parental Bonding Inventory (PBI) and measures of criticism. Parental care, overprotection and country were found to be significant predictors of a tendency to perceive criticism as destructive. Higher levels of parental care predicted a lower tendency to perceive criticism as destructive while higher levels of parental overprotection predicted a higher tendency to perceive criticism as destructive. US American participants were found to have a significantly higher tendency to perceive criticism as destructive compared to Italian and Singaporean participants. The findings align with past research on the role of the parent-child relationship in the socio-emotional development of children as well as providing insight into a specific aspect in social interaction; perception and response to criticism, being affected. Future studies can look to investigate this relationship further in different countries in light of cultural variation in parenting styles and emotion experience, expression and regulation.